Modulating tibiofemoral contact force in the sheep hind limb via treadmill walking: Predictions from an opensim musculoskeletal model. Issue 8 (28th May 2015) - Lerner, Zachary F.; Gadomski, Benjamin C.; Ipson, Allison K.; Haussler, Kevin K.; Puttlitz, Christian M.; Browning, Raymond C.
ABSTRACT Sheep are a predominant animal model used to study a variety of orthopedic conditions. Understanding and controlling the in‐vivo loading environment in the sheep hind limb is often necessary for investigations relating to bone and joint mechanics. The purpose of this study was to develop a musculoskeletal model of an adult sheep hind limb and investigate the effects of treadmill walking speed on muscle and joint contact forces. We constructed the skeletal geometry of the model from computed topography images. Dual‐energy x‐ray absorptiometry was utilized to establish the inertial properties of each model segment. Detailed dissection and tendon excursion experiments established the requisite muscle lines of actions. We used OpenSim and experimentally‐collected marker trajectories and ground reaction forces to quantify muscle and joint contact forces during treadmill walking at 0.25 m s−1 and 0.75 m s−1. Peak compressive and anterior–posterior tibiofemoral contact forces were 20% (0.38 BW, p = 0.008) and 37% (0.17 BW, p = 0.040) larger, respectively, at the moderate gait speed relative to the slower speed. Medial–lateral tibiofemoral contact forces were not significantly different. Adjusting treadmill speed appears to be a viable method to modulate compressive and anterior–posterior tibiofemoral contact forces in the sheep hind limb. The musculoskeletal model is freely‐available at www.SimTK.org. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1128–1133, 2015.